Farmers and their aspirations : influence of socio-economic status and work orientation - Muthayya. B. C. (Hyderabad, 1971)
STUDY of aspirations is of paramount importance in a developing country like India as it would give an idea of the type of life the people look forward to. The study reported here attempts to assess the nature and extent of aspiration in certain areas of the life situation of the farmer-cultivators in a few villages of Rajendranagar block of Andhra Pradesh, It also examines the aspirations in the light of two basic factors, namely, socio economic status and work-orientation of the farmers, with a view to under stand the extent of their influence in the determination of their aspirations, Based on the findings of the study, certain suggestions are offered for the development of aspirations on realistic lines so that every aspiration becomes an achievement, thereby enhancing one's self-confidence and self-reliance
Keywords: Farmers